Pembelajaran Teori Musik Secara Daring Menggunakan Model Pembelajaran Student Team Achievement Division (STAD) - Yudi Sukmayadi (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2022)
The online learning situation certainly requires special adjustments in the field of education. In Junior High School the learning strategy applied by the teacher must be effective in the learning process, so that it can achieve the expected final results. This study aims to reveal online learning strategies in the Cultural Arts class with Music Theory at Sultan Iskandar Muda Junior High School, Medan. Qualitative research with a descriptive approach in explaining the findings of information in the field. The results of this study are there are 3 strategies used by teachers, namely 1) direct learning strategies, 2) indirect learning strategies, and 3) independent learning strategies, using a student-centered learning approach as the subject of study. This online learning strategy is quite effective, because students are not only able to find one starting sign of one scale, but also various starting signs of one scale. The learning strategy carried out by the supporting teacher also makes it easier for students to understand the concept of early signs.